PENINGKATAN KREATIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MELALUI METODE PROJECT BASED LEARNING - Sri Suwartini; Siti Maisyaroh; Agus Supatno; Anindi Putri Safira Wulandari; Apri Faridah Laelatun Nikmah; Apriafel Gilang Budi Paranto; Benii Ardliana; Dian Indriati Bella Santoso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low creativity and learning outcomes of fifth-grade students of SDN Tangkisan Pos in the subject of Science, especially in the material of the Human Respiration Process. This study aims to improve creativity and student learning outcomes through the application of the Project Based Learning (PjBL) method based on the creation of respiratory teaching aids. This type of research is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of four main stages: planning, implementation of actions, observation, and reflection. The subjects of this study were 28 fifth-grade students of SDN Tangkisan Pos in second semester of 2025/2026 academic year. Data collection techniques were carried out through written tests, student creativity observation sheets, teacher activity observation sheets, and documentation. The results of study showed a significant increase after the application of the Project Based Learning method. The percentage of classical learning outcome completion increased from 28.57% in the pre-cycle stage, to 82.14% in Cycle I, and reached a success indicator of 100% in Cycle II. In line with learning outcomes, the average value of students' creativity in designing, making, and presenting projects also increased from the Sufficient category in the pre-cycle to the Very Good category at the end of Cycle II. Based on these results, it can be concluded that implementation of the Project Based Learning method has proven effective in improving students' creativity and learning outcomes in the Human Respiration Process material in class V SDN Tangkisan Pos.